Extractivism and Territorial Dispossession in Rural Colombia: A Decolonial Commitment to Campesinas' Politics of Place. Issue 1 (July 2021) - Rodriguez Castro, Laura
Linked to extractive practices, territorial dispossession can be traced back to the colonisation of Abya Yala. From a decolonial commitment, this article complicates notions of dispossession and extractivism as merely emerging from war in Colombia and focuses on their presence in Campesinas territories. Based on the conceptualisations of the coloniality of power and coloniality of gender, I narrate how territorial dispossession and extractivism are felt in women's 'body-lands' through foreign tourism/conservation development and new export crops in two rural veredas in the Colombian Andes and in the Sierra Nevada de Santa Marta where I conducted participatory visual projects in 2016. From a relational understanding of place, I also demonstrate the ways that the rural population is resisting and negotiating within these processes. Ultimately, I make a call for feminist scholars to politically commit to the dismantling of the coloniality of gender, and to the resistances to territorial dispossession and extractivism (epistemic and economic) that rural women are leading in place in the Global South.